Overview of Knowledge and Behavior of Clean and Healthy Living Patterns Post Flood - Aisyah Indriyana; Tri Susilowati (Universitas Duta Bangsa Surakarta, 2026)
Pucangsawit Village is the area with the highest incidence of flooding in the City of Surakarta, occurring up to six times per year, which increases the risk of health problems due to limited access to clean water and environmental sanitation. This condition highlights the importance of implementing Clean and Healthy Living Behavior as a preventive measure against post-disaster health issues. This study aimed to describe the level of knowledge and behavior related to Clean and Healthy Living Behavior among the community after flooding in Pucangsawit Village, Jebres District, Surakarta. A descriptive study with a quantitative approach was conducted. A total of 54 respondents were selected using proportional random sampling. Data were collected through questionnaires and analyzed using univariate analysis. The results indicated that a majority of respondents had a high level of knowledge (83.3%) and demonstrated good practices (59.3%) regarding Clean and Healthy Living Behavior. These findings suggest that the community has adequate understanding and implementation of healthy living practices after flooding. It can be concluded that good knowledge plays an important role in shaping healthy behavior; therefore, continuous monitoring and health education are necessary to maintain and improve the application of Clean and Healthy Living Behavior in preventing health problems following flood disasters.